Correlation between OSH Perception and Knowledge with Safety Behavior in Subcontractor Workers at PT Yasa Wahana Tirta Samudera Semarang - Aura Chantiqa Niantiara; Seviana Rinawati; Istar Yuliadi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
PT Yasa Wahana Tirta Samudera is an industry which operates in ship building and repair by subcontractor workers. Safety behavior of subcontractor workers still found unsafe behavior by subcontractor workers. The purpose of this research is to find out there is a correlation between OHS perception and knowledge with safety behavior subcontractor workers in PT Yasa Wahana Tirta Samudera. This research used an observational analythical method with cross sectional approach. The sample in this research were 100 subcontractor workers by simple random sampling. Based on somers’d test , it is known that p value = 0.000 (p < 0.05) means that there is a significant correlation between OHS perception with safety behavior, and a significant correlation between OHS knowledge with safety behavior. The result of ordinal logistic regression obtained that OR = 5.999 means that OHS knowledge is greater influence than OHS perception. From this research it can be concluded that OHS knowledge affects 5.999 times on the safety behavior subcontractor workers PT Yasa Wahana Tirta Samudera. The researcher suggest for further research to analyze other variables which have not been controlled in this research.